ChemInform Abstract: Copper‐Catalyzed Tandem A3‐Coupling—Isomerization—Hydrolysis Reactions of Aldehydes and Terminal Alkynes Leading to Chalcones. Issue 27 (16th June 2016) - Zhao, Yingwei; Song, Qiuling
Abstract: Rare examples for an A 3 ‐coupling leading to chalcones are reported.